Serotonin Levels in Attention Deficit Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The relationship between blood serotonin, norepinephrine, dopa and lipid levels and the degree of hyperactivity, impulsiveness, inattention, and aggressiveness in 35 boys with ADHD, combined type, was studied at the Ness Ziona Mental Health Center, Nes Zona, Tel Aviv University, and other centers in Israel.